Inefficient incentives for energy saving in tenancy law and policy options to remedy the landlord-tenant-dilemma - Leo Florian Reutter (Philipps-University Marburg, School of Business and Economics, 2024)
The rental building sector is plagued by the so-called landlord-tenant-dilemma, i.e. that landlords have no direct financial benefit from modernizations for energy efficiency if the tenant pays the energy bill while tenants have no incentives to save energy if the landlord pays. The primary landlord-tenant-dilemma occurs due to rent control limiting rent levels in incumbent tenancies and the secondary land-lord-tenant-dilemma stems from modernization costs being sunk and thus not reflected in the bargaining over rent levels when a new rental contract is negotiated after a modernization. Tenancy law with an allocation system for energy and modernization costs can help remedying these issues or exacerbate them. This paper develops an analytical model to study how efficiently different allocation systems set modernization and frugality incentives and which ones compare favorably against each other in terms of landlords', tenants', and their combined welfare. I scrutinize a free market, the Swedish inclusive rent system, the German status quo, a slight variation to the German status quo, a consumption based partially inclusive rent system, and a novel demand based partially inclusive rent system. The German status quo actually can theoretically set optimal incentives if it could be setup ideally but it interacts peculiarly with the rest of German tenancy law, impeding optimal design. The demand based partially inclusive rent system could more reliably set efficient incentives but requires a more radical reform of tenancy law.
Keywords: D61; D86; K25; 330; Landlord-tenant-dilemma; tenancy law; energy efficiency; split-incentive-problem